Normosmic idiopathic hypogonadotropic hypogonadism due to a novel homozygous nonsense c.C969A (p.Y323X) mutation in the KISS1R gene in three unrelated families. (7th November 2014) - Demirbilek, Huseyin; Ozbek, M. Nuri; Demir, Korcan; Kotan, L. Damla; Cesur, Yasar; Dogan, Murat; Temiz, Fatih; Mengen, Eda; Gurbuz, Fatih; Yuksel, Bilgin; Topaloglu, A. Kemal
Summary Objective The spectrum of genetic alterations in cases of hypogonadotropic hypogonadism continue to expand. However, KISS1R mutations remain rare. The aim of this study was to understand the molecular basis of normosmic idiopathic hypogonadotropic hypogonadism. Methods Clinical characteristics, hormonal studies and genetic analyses of seven cases with idiopathic normosmic hypogonadotropic hypogonadism (nIHH) from three unrelated consanguineous families are presented. Results One male presented with absence of pubertal onset and required surgery for severe penoscrotal hypospadias and cryptorchidism, while other two males had absence of pubertal onset. Two of four female cases required replacement therapy for pubertal onset and maintenance, whereas the other two had spontaneous pubertal onset but incomplete maturation. In sequence analysis, we identified a novel homozygous nonsense (p.Y323X) mutation (c.C969A) in the last exon of the KISS1R gene in all clinically affected cases. Conclusions We identified a homozygous nonsense mutation in the KISS1R gene in three unrelated families with nIHH, which enabled us to observe the phenotypic consequences of this rare condition. Escape from nonsense‐mediated decay, and thus production of abnormal proteins, may account for the variable severity of the phenotype. Although KISS1R mutations are extremely rare and can cause a heterogeneous phenotype, analysis of the KISS1R gene should be a part of genetic analysis of patients with nIHH, to allow better understanding of phenotype–genotype relationship of KISS1R mutations and the underlying genetic basis of patients with nIHH.